APCB’s Abstracts 3: 9th Asian Pacific Congress on Bronchology and Interventional Pulmonology - Asia-Pacific Congress Bronchology-Interventional Pulmonology (The Interventionalist Journal, 2023)
APCB’s Abstracts 3 1. EP06: FLEXIBLE BRONCHOSCOPY FOR THE EXTRACTION OF ASPIRATED STRAIGHT PIN IN CHILDREN 2. EP07: OUTCOMES OF SLIDE TRACHEOPLASTY IN CONGENITAL TRACHEAL STENOSIS: A 10-YEAR EXPERIENCE 3. EP08: FRONTIERS IN MANAGING BENIGN CENTRAL AIRWAY STENOSIS: THE FIRST CASE OF BIODEGRADABLE AIRWAY STENT IN ASIA 4. E0P09: THE RELATIONSHIP BETWEEN RADIATION EXPOSURE AND THE EXPOSURE REDUCTION EFFECTI OF THE PROTECTIVE GLASSES DURING BRONCHOSCOPY USING A C-ARM X-RAY FLUOROSCOPY SYSTEM